Eating Beyond Ecology: The Impacts of Hunting Technologies on Archaeofaunas from the Eastern Arctic - Howse, Lesley Ruth (2018)
This dissertation explores human-animal relationships within two very different societies, Late Dorset (500 CE to 1300 CE) and Thule Inuit (1200 CE to 1500 CE), who occupied common geographical areas throughout the eastern Arctic. While scholars interested in the behaviour of Northern hunter-gatherers have tended to focus on the primacy of environmental factors and changing environments, this dissertation aims to achieve a more nuanced understanding of the role of cultural factors in shaping human-animal interaction. I pursue this goal by focusing on distinct Late Dorset and Thule Inuit hunting technologies and practices, using zooarchaeological analyses to directly examine their impacts on subsistence strategies, including encounter rates, labour strategies, resource scheduling, and diet breadth. To address marked variability in resource availability between different areas in the eastern Arctic and allow for a cross-Arctic comparison, I consider three separate regions where Late Dorset and Thule Inuit occupied either the same site or sites that are located in close proximity. Although hunting strategies in each region were greatly influenced by regionally-specific environments, I argue that this research shows they are also culturally distinct. Results suggest that differences in Late Dorset and Thule Inuit hunting technologies impacted their archaeofaunas in various ways, they directly influenced each groups hunting strategies, and ultimately, helped shape the human-animal relationship in each society. In comparison to Thule Inuit, Late Dorset were constrained by their hunting technologies, having to rely more heavily upon specific types of terrain features and seasonal changes in the environment. Thule Inuit hunting technologies, by contrast, allowed for larger harvests of key resources, providing better provisioning and perhaps an increase in food security. These results serve to highlight the role of culture in prehistoric lifeways, even in â marginalâ environments. Ph.D. 2018-11-30 00:00:00